Do higher educated people feel happier?—Evidence of Han and minority nationalities from China - Yuanyuan Wang; Zhenyi Hu; Jiameng Yuan; Kun Zhang (PLoS ONE, 2025)
Based on the data of China General Social Survey (CGSS), this study adopts empirical analysis method to explore the impact of education on residents’ subjective well-being and its differentiated mechanism in different ethnic groups. The results show that, first of all, education significantly improves residents’ subjective well-being, and the conclusion is still robust after controlling for endogenous problems. Secondly, compared with Han nationality, education has a more significant effect on the subjective well-being of ethnic minority residents. Finally, by comparing the internal mechanism of education on the subjective well-being of Han and ethnic minority residents, the research finds that education mainly improves subjective well-being by improving residents’ relative income level and enhancing their social class identification, in which the intermediary effect of income is particularly prominent. However, in the Han population, education may weaken the sense of fairness, and thus reduce happiness to some extent; This phenomenon has not been verified in ethnic minority groups. This study not only expands the literature on the relationship between education and subjective well-being, but also has important policy implications, providing a strong empirical basis for formulating more accurate education policies, improving the happiness of ethnic minority residents, and enhancing national cohesion.